City Space : Sculptures and installations made for Copenhagen 96. - Andersen, Mikael; Arndal, Vicky Lea; Balka, Miroslaw; Bang, Lars; Dercon, Chris; Geoffroy/Colonel, Thierry; Huyghe, Pierre; Kern, Kristine; Kvorning, Jens; Llambias, Pablo; Nilsson, John Peter; Osterby, Anette; et al. (Kobenhavn, : City, 1996)
Adams, Dennis ; Andersen, Henrik B. ; Art, Scale ; Bäcklund, Jan ; Balka, Miroslaw ; Brinch, Jes ; Broager, Ole ; Buren, Daniel ; Graham, Dan ; Haaning, Jens ; Huyghe, Pierre ; Jensen, Soren ; Kirkeby, Per ; Muñoz, Juan ; Nygard, Oivind ; Paraponaris, Hervé ; Parker, Cornelia ; Rollof, Ulf ; Straede, Morten ; Streuli, Beat ; Tuerlinckx, Joëlle ; Vos, Giny ; Werner, Agneta
Engels & Deens
City Space : Sculptures and installations made for Copenhagen 96, 15.05 - 01.10.1996
boek